Propuesta para el diseño y la planificación de la ruta turística-gastronómica del cangrejo en la provincia del Guayas. - Mena Molina, Ma. Isabel (2010)
This study is conducting a gastronomic route in the province of Guayas, which highlights the potential of the crab as a coast’s typical dish, in the land segment which connects several places of it’s catch, wholesale and retail sale, starting in Naranjal, where is located the 25 de Julio (catch area), the cueva del cangrejo (retail sale site) and the Naranjaleño crab tourist location (wholesale site). Moreover in Duran sector is located the Plaza del Cangrejo Pelucón, which is a sale site of the specie. In Guayaquil are the most of crab restaurants with tourist attraction nearby. The design of the route was reached throw sequential steps divided in three chapters, starting with a investigation of the current situation of the province, both geographically and socio-economic, followed by a study on the target market or demand of potential tourists through surveys to investigate the crab outlets and the preparation of its dishes. Subsequently, the study results gave prominent ideas to create the design of the route, the logo and brochure. All of the proposals above generated as a result aesthetic improvement of the places of sale of crab as well as offering created on potential tourists´s based tastes.